Strengthening Culinary Micro-Enterprises Competitiveness Through SWOT Analysis and Business Model Canvas - Ardiansyah, Ardiansyah (International Journal Papier Public Review, 2024)
The research objective is to analyze the culinary business situation in the city of Sintang and recommend new business strategies to increase the competitiveness of the culinary business. The method in this research is a mix method, namely combining a quantitative survey with many respondents to obtain SWOT input data and business models, with in-depth qualitative interviews with several key informants to deepen the survey results. The sample in the research was 150 culinary micro business actors using a purposive sampling technique. The results of research using the canvas business model are that culinary micro businesses have broad customer segments. Relations with consumers are direct and good. The value proposition is carried out by prioritizing product quality to improve performance. The main activity is marketing its products directly. Collaboration is carried out with several government and private offices in the city of Sintang. Costs used, fixed costs and variable costs and sole income from direct and online product sales. The SWOT analysis used to assess internal and external factors produces respective external and internal factor scores, where the internal strength factor scores 1.65, the internal weakness factor scores 1.01, the external opportunity factor scores 1.50, and the external threat factor scores 1.05. Based on the diagram, the culinary micro business strategy in Sintang city is in quadrant one, which means it supports aggressive strategies.